PENGARUH MEDIA DIGITAL PHET INTERACTIVE SIMULATION TERHADAP PARTISIPASI SISWA DALAM PEMBELAJARAN IPAS KELAS V DI SDN 12 BIRAENG KABUPATEN PANGKEP - Sakirah Fhasihah; Amir Pada; Yusnadi S (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The Influence of PhET Interactive Simulation Digital Media on Student Participation in Grade V Science and Social Studies Learning at SDN 12 Biraeng, Pangkep Regency, is a quantitative quasi-experimental study with a Non-equivalent Control Group Design. This research addresses the low participation of fifth-grade students who tended to be passive in learning. The study involved 46 students from experimental (VA, n=24) and control (VB, n=22) groups. Data were collected through questionnaires and observation sheets, then analyzed using descriptive and inferential statistics. The findings reveal that the implementation of PhET Interactive Simulation was effectively executed, creating an interactive and student-centered learning environment. Student participation in the experimental class significantly improved from low to very high category, with a much greater increase compared to the control group. Hypothesis testing using Independent Sample t-Test showed a significance value of 0.000 (p < 0.05), while Paired Sample t-Test resulted in a mean difference of -30.042 with Sig. (2-tailed) = 0.000 (p < 0.001), confirming a statistically significant increase in student participation. This research concludes that there is a significant influence of PhET Interactive Simulation digital media on student participation in grade V science and social studies learning at SDN 12 Biraeng, Pangkep Regency.